Analisis Krisis Keuangan ASIA 1997: Penyebab, Dampak, dan Pemulihan Ekonomi di Indonesia - Rifadli D. Kadir (Jurnal Ekonomi Islam, 2025)
The 1997 Asian financial crisis had a profound impact on the economies of Asian countries, including Indonesia. The crisis began with the depreciation of Thailand's Baht, which spread to neighboring countries, destabilizing the economies of Indonesia, Thailand, and South Korea. A sharp decline in currency values, high interest rates, and a banking crisis led to economic uncertainty across sectors. The primary cause of the crisis was the "hot money bubble," a speculative capital flow, exacerbated by weak banking systems and reliance on an unstable exchange rate system. In response to the crisis, Indonesia borrowed from the IMF, which initiated a series of economic reforms, including macroeconomic stabilization and financial system reforms. Despite various reform efforts, the implementation faced significant challenges due to political instability and a lack of coordination among government institutions. The post-crisis recovery highlighted the importance of improved financial risk management and political stability for sustaining economic development. This article aims to provide a comprehensive understanding of the factors that led to the crisis, its impacts, and the recovery efforts undertaken in Indonesia after the 1997 crisis.